Tedhak Siten: an Islamic-Javanese Acculturation - Rika Yuliastanti; Parwita Setya Wardhani; Dyah Ayu Lestari (Yayasan Rumah Peneleh, 2022)
This study aims to investigate one specific tradition of Indonesia, namely Tedhak Siten as an acculturation of Islamic and Javanese values and practice. The Javanese are the largest ethnic group in Indonesia. Tedhak Siten comprises a series of traditional traditional processions to recognize a stage of childhood when it is the first time a child learns to set foot on the ground. Through a qualitative study, it was found that up to this day, the Javanese people still hold this ceremony even though it is in the modern era. In addition to reasons of belief, Javanese people are famous for their love for culture or customs handed down by their ancestors. The series of events include walking on colored glutinous rice, climbing stairs made of sugarcane, entering a chicken coop, picking objects, fighting over coins, and taking a flower bath. Each of these rituals has its own meaning and purpose for the future of the child. Although some people claim that Tedhak Siten is not mandatory, some continues to hold this ceremony, and some has abandoned this custom. This indicates that there is shift in the value of a culture or tradition is due to the development of modernization, which then replaces the long-cherished culture.